Establishment of an in vivo analytical method for detecting total anti-UFH activity and pharmacokinetic study in PS and R15 in rats - Huimin Li; Tong Li; Zhiyun Meng; Xiaoxia Zhu; Ruolan Gu; Hui Gan; Guifang Dou (PLoS ONE, 2025)
Protamine sulfate (PS), the only U.S. Food and Drug Administration (FDA)-approved heparin antagonist, is encumbered by several drawbacks. R15, a synthetic polyarginine peptide, has proven to be a promising protamine substitute in prior studies. PS and R15 undergo biotransformation to active metabolites, underscoring the need for an analytical method that quantifies their total anti-heparin activity in vivo. Here, we reported the development and validation of such a method and described the pharmacokinetic profiles of PS and R15 in rats. Total anti-heparin activity in plasma was quantified by fortifying each sample with a fixed concentration of heparin and subsequently measuring the residual heparin. The method was fully validated for PS and R15 in accordance with Chinese bioanalytical guidance from Chinese Pharmacopoeia, confirming acceptable selectivity, precision and accuracy, stability, and dilution integrity. Pharmacokinetic profiles were then characterized in rats following single intravenous bolus administrations of PS at 300 U·kg ⁻ ¹ and R15 at 300, 900, and 2700 U·kg ⁻ ¹. An assay for quantifying total anti- heparin activity in rat plasma was successfully validated for both PS and R15. After a single intravenous dose of 300 U·kg-1, R15 sustained anti-heparin activity for a markedly longer period (51.93 min vs. 3.94 min) and achieved an 18-fold higher of areaunder the curves (AUC = 632 min·μg·mL-1 vs. 35.89 min·μg·mL-1) with 19-fold higher mean residence time (MRT = 54.95 min vs. 2.59 min). Clearance (CL) for R15 and PS was 2.73 mL·min-1·kg-1 vs. 53.65 mL·min-1·kg-1, whereas the apparent volume of distribution (Vd) was of similar level (194 mL·kg-1 vs. 268 mL·kg-1), consistent with limited tissue distribution and prolonged intravascular retention. The extended exposure afforded by R15 is clinically advantageous because it mitigates the well-documented “heparin rebound” observed after rapid protamine clearance, thereby reducing the need for repeat dosing. R15 exhibited dose-dependent nonlinear pharmacokinetics, demonstrating saturable elimination processes typical of nonlinear pharmacokinetics. The validated assay, coupled with the in vivo rat pharmacokinetic study, provides a solid foundation for advancing R15’s preclinical development.